Fundamentalismo bíblico protestante: abordagem histórica e implicações sociorreligiosas - Guimarães, Valtemir Ramos (2014)
This paper aims, in general, at analyzing the Biblical Fundamentalism socioreligious phenomenon, since its origin, within the ninetieth century Northamerican Protestantism, until our days which we observe in its Fundamentalism´s strong presence, overall in the Protestantism´s inner life. Paradoxically, in spite of all scientific and technological advancement that is observed in these recent last years, which have given beginning to the twenty first century, Fundamentalism has grown up in all so-called Book Religions: Judaism, Christianism and Islamism. And this is not true only in the religious circles, but also in other society sectors, including the political ones. Regarding to the Biblical Fundamentalism, present in protestant communities, we can observe positive and negative aspects which will be properly analyzed throughout this work. In this perspective, we have tried researching the Fundamentalism´s assumptions, development and dissemination, since its origin within American Protestantism in the late ninetieth century in order to understand its socioreligious implications for the present days. The applied methodology consists of studies and researches, departing from specialized bibliography, based on the academic environment in History, Sociology, Anthropology, Theology, Exegesis and Biblical Hermeneutics area, departathing from protestant and catholic authors who transit thoughout the Sciences concerning Religion epistemological field. Departing from pertinent informations regarding to the present time, we acknowledge that the Biblical Fundamentalism has grown and impacted, day after day, in the ecclesiastical environment which is evident in its praxis in Brazil and in the world. We may conclude that this studies subject reflectes in the relationships concerning family, the communities and society, amid the challenges regarding to the modernity in crises.